ELM-induced transient tungsten melting in the JET divertor. (21st January 2015) - Coenen, J.W.; Arnoux, G.; Bazylev, B.; Matthews, G.F.; Autricque, A.; Balboa, I.; Clever, M.; Dejarnac, R.; Coffey, I.; Corre, Y.; Devaux, S.; Frassinetti, L.; et al.
Abstract: The original goals of the JET ITER-like wall included the study of the impact of an all W divertor on plasma operation (Coenen et al 2013 Nucl. Fusion 53 073043 ) and fuel retention (Brezinsek et al 2013 Nucl. Fusion 53 083023 ). ITER has recently decided to install a full-tungsten (W) divertor from the start of operations. One of the key inputs required in support of this decision was the study of the possibility of W melting and melt splashing during transients. Damage of this type can lead to modifications of surface topology which could lead to higher disruption frequency or compromise subsequent plasma operation. Although every effort will be made to avoid leading edges, ITER plasma stored energies are sufficient that transients can drive shallow melting on the top surfaces of components. JET is able to produce ELMs large enough to allow access to transient melting in a regime of relevance to ITER. Transient W melt experiments were performed in JET using a dedicated divertor module and a sequence of I P = 3.0 MA/ B T = 2.9 T H-mode pulses with an input power of P IN = 23 MW, a stored energy of ∼6 MJ and regular type I ELMs at Δ W ELM = 0.3 MJ and f ELM ∼ 30 Hz. By moving the outer strike point onto a dedicated leading edge in the W divertor the base temperature was raised within ∼1 s to a level allowing transient, ELM-driven melting during the subsequent 0.5 s. Such ELMs ( δ W ∼ 300 kJ per ELM) are comparable to mitigated ELMs expected in ITER (Pitts et al 2011 J. Nucl. Mater. 415 (Suppl.) S957–64 ). Although significant material losses in terms of ejections into the plasma were not observed, there is indirect evidence that some small droplets (∼80 µ m) were released. Almost 1 mm (∼6 mm 3 ) of W was moved by ∼150 ELMs within 7 subsequent discharges. The impact on the main plasma parameters was minor and no disruptions occurred. The W-melt gradually moved along the leading edge towards the high-field side, driven by j × B forces. The evaporation rate determined from spectroscopy is 100 times less than expected from steady state melting and is thus consistent only with transient melting during the individual ELMs. Analysis of IR data and spectroscopy together with modelling using the MEMOS code Bazylev et al 2009 J. Nucl. Mater. 390–391 810–13 point to transient melting as the main process. 3D MEMOS simulations on the consequences of multiple ELMs on damage of tungsten castellated armour have been performed. These experiments provide the first experimental evidence for the absence of significant melt splashing at transient events resembling mitigated ELMs on ITER and establish a key experimental benchmark for the MEMOS code.